The memory thief - Anderson, Jodi Lynn (Anderson, Jodi Lynn. Thirteen witches, 2021)
When sixth-grader Rosie begins to see magic, she learns that her mother's dwindling memory is tied to an age-old battle between the light of the moon and the darkness of witches.